Susun Kata Tingkatkan Literasi: Pelatihan Kreatif bagi Anak-Anak Kampung Onggatmit - Uskenat, Kristina; Simbolon, Merta; Yuliatun, Tutik (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
The quality of education in Indonesia is still low, one of the causes is the low ability to read, in this case reading literacy and critical thinking skills, especially in children. This is based on data that Papua Province ranks last with a score of 19.90 which shows a very low category. Onggatmit Village is one of the villages in Merauke, South Papua Province with many children who are still unable to read and even recognize letters and numbers. Basic literacy needs to be applied early in primary school-age children when brain development can still be shaped. Due to conditions that cannot gain knowledge in school, one of the activities that can be done to improve basic literacy is to conduct basic literacy training for children in Onggatmit Village with word stacking games. This service activity was carried out in four stages, namely survey, socialization, training and monitoring. The results of this service activity run smoothly and can improve basic literacy skills carried out with word stacking games for children in Onggatmit Village.